2019
DOI: 10.1080/23322039.2019.1636496
|View full text |Cite
|
Sign up to set email alerts
|

Are structural policies in countries bordering mediterranean appropriate to economic convergence: Panel ARDL application

Abstract: Our main contribution in this paper consists of analyzing long-run interactions between structural policies and economic growth accounting for possible convergence. For this purpose, we are based on a sample of eight countries bordering the Mediterranean during the period 1975-2012. In fact, we used a technique based on panel ARDL methods which deals with the stationary series problem of different orders to monitor possible convergence in the longrun horizon. This method allows us to study potential long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The sign of foreign direct investment is negative and significant. Due to the FDI entering to Tunisia is not very capital intensive; result can be explained, generally related to the textile sector (Ayouni and Bardi [2018] and Bardi et al [2019]). In addition, the corruption index has a positive and statistically significant coefficient.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…The sign of foreign direct investment is negative and significant. Due to the FDI entering to Tunisia is not very capital intensive; result can be explained, generally related to the textile sector (Ayouni and Bardi [2018] and Bardi et al [2019]). In addition, the corruption index has a positive and statistically significant coefficient.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Third the variable of trade is positive and promotes the growth and increase the poverty (Bardi and Hfaied (2021)) and investment variable reduce the poverty and increase the economic growth (Bardi et al (2019) and Ayouni and Bardi (2018)) in our sample of countries.…”
Section: Conclusion and Policy Implicationmentioning
confidence: 84%
“…It can thus be concluded that a null hypothesis cannot be rejected, and the PMG estimator is preferred. Under the null (slope homogeneity), the PMG estimator is consistent and efficient (Bardi et al 2019). The study only reports the findings from the PMG estimator because the Hausman test chose it as the preferred model.…”
Section: Regression Resultsmentioning
confidence: 99%